Efeito do peso de abate, do tipo de corte e do grupo genético na qualidade da carne de caprinos do estado do Ceará. - Aguiar, Luciana Fujiwara de (2001)
In this study, it evaluated was the influence of two different types of weight and cut, and also the kind of cut involving four types of treatment: treatment 1(ANGLONUBIANO x SRD and weight ranging 20-22 kg), treatment 2 (ANGLONUBIANO x SRD and weight ranging 26-28 kg), and treatment 3 (BOER x SRD, weight rancing 20-22 kg) and 4 (BOER x SRD, weight rancing 26-28 kg) involving some characteristics of centesimal composition, fatty acids and cholesterol of goat meat belonging to related genetic group, recently introduced in the state of Ceará. Leg, shoulder and loin cuts of 12 animals with distinct weights, bred in semi-intensive regime, fed with maize and soy (70:30 proportion) protein concentrate were used. Proximal composition analysis showed average values of moisture from 75.95 to 77.50%; 18.81 to 22.98% for protein; 0.70 to 1.35% for fat and 1.01 to 1.15% for ash. Significant differences were found between treatment 2 (ANGLONUBIANO x SRD and weights between 26 and 28 kg) and treatment 3 (BOER x SRD and weight between 20 and 22 kg), for protein in shoulder cut and for ash in pernil cuts and loin. In relation to cholesterol analysis, general average values for leg, shoulder and loin were situated between the following values: 31.60 to 59.16%; 34.79 to 61.34% and 32.79 and 59.72%, respectively, corresponding to the range form 19.36 to 65.32 mg/100g of meat. Higher cholesterol values were observed for treatment 4 (BOER x SRD and weight form 26 to 28 kg) in all cuts, except for treatment 1. Effect of genetic group was statistically (p<0.05) observed between treatments 2 and 4 in all cuts. In fatty acids composition analysis, 8 peaks were identified in all treatments. Four were saturated (miristic, palmitic, stearic and arachidic) and four unsaturated (palmitoleic, oleic, linoleic and linolenic). Oleic acid (23.89 to 31.04%), stearic (16.83 to 24.97%), palmitic (15.82 to 24.23%) and linoleic (7.41 to 16.81%) were the main fatty acids found. Significant differences (p<0.05) were found between cuts and treatments for miristic, palmitic, palmitoleic, linolenic and arachidic acids. Saturated/unsaturated ratio did not show any significant difference (p<0.05) among treatments or cuts.